1997
DOI: 10.3758/bf03211870
|View full text |Cite
|
Sign up to set email alerts
|

Visual detection and perceptual independence: Assessing color and form

Abstract: Visual stimuli are multidimensional. One important perceptual problem is to determine how the dimensions are combined. One important aspect of dimensional combination is whether the dimensions are perceptually independent or perceptually correlated. Anew task is presented-the visual detection task-that directly assesses the degree of perceptual correlation between any two dimensions. Two experiments were conducted that assess the degree of perceptual correlation between form and color during the early stages o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 49 publications
(78 reference statements)
4
38
0
Order By: Relevance
“…The present experiment is an extension of Cohen (1997). Cohen reported a visual detectionexperiment that provided evidence that color and form are not detected independently in early vision.…”
Section: Methodsmentioning
confidence: 95%
See 2 more Smart Citations
“…The present experiment is an extension of Cohen (1997). Cohen reported a visual detectionexperiment that provided evidence that color and form are not detected independently in early vision.…”
Section: Methodsmentioning
confidence: 95%
“…Each analysis was first calculated on the individual participant's data and then concatenatedacross participantsusing a summedz meta-analysis (for a detailed description of the analysis, see Cohen, 1997;Rosenthal & Rubin, 1986;Strube, 1985;Strube & Miller, 1986). The summed-z meta-analysis was appropriate because the degrees of freedom associated with each t test were large enough for the t distribution to be a good approximation of a Gaussian.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multimodal signals enhance signal performance through intersensory facilitation, while unimodal multicomponent signals mainly improve the specificity of the information received along a single sensory channel, although the components can interact in a similar manner to those in bimodal compounds (Cohen, 1997;Aydin & Pearce, 1997).…”
Section: (5) Receiver Psychologymentioning
confidence: 99%
“…In a series of seven experiments studying preattentive vision we (Cohen 1997;Kubovy et al, in press) have collected considerable evidence in favor of our theory. In these studies we have shown that (1) when different feature dimensions form coincident boundaries, these boundaries are detected better than would be expected if the modules were independent; (2) when different feature dimensions form inconsistent boundaries, these boundaries are detected more poorly than would be expected if the modules were independent.…”
Section: Even Feature Integration Is Cognitively Impenetrablementioning
confidence: 99%